Overview of Learning Evaluation in Entrepreneurship Subjects Equality Education Paket C - Syuraini, Syuraini; Yolanda, Yolanda (Journal of Nonformal Education, 2019)
This research is backed by the high percentage of people’s graduation to learn to take national examinations of computer standards and school exams in national standards. This research aims to illustrate the implementation of the learning evaluation conducted by tutors at the community leaning Centers Farilla Ilmi. This research form ex post facto with population learning C package as much as 60 people. Samples were pulled as many as 30 people using a stratified random sampling technique. Data is collected using poll techniques and analyzed using a percentage formula. The results of the study showed (1) package C tutors at the community learning centers Farilla Ilmi very varied, there are already graduates who are still students and some are only having a senior secondary school diploma but have a certificate of training A lot. (2) The evaluation of learning conducted by tutors performed very well. The evaluation is conducted comprehensively ranging from assessing the readiness of the citizens to learning, assessing the learning process, and assessing the learning outcomes of oral learners, writings and practices. The benefits that can be learned from the findings of this study are the existence of tutors who are young and generally almost the same age as the citizens learn so that the citizens learn not shy and very excited about following the lesson. The newness factor here that most tutors are recruited from Padang State University students who already carry out the teaching practice. Thus, the teaching tutor is ideal according to what it is practiced in school as a prospective teacher.